Habitus dan Tantangan Sosiokultural dalam Tata Kelola Koperasi Desa Merah-Putih di Pedesaan Lampung: Sebuah Studi Antropologi Pembangunan - Bartoven Vivit Nurdin; Rezha Marsya Nabila; Damar Wibisono; Syifaa Sabionova Addina Turki (Jurnal Bina Praja, 2026)
This study analyzes the habitus and socio-cultural challenges in the governance of Red-and-White rural village cooperatives in rural Lampung from the perspective of the anthropology of development. Cooperatives are understood not only as economic entities but also as social spaces shaped by local values, norms, power relations, and cultural practices, and many development programs falter when these dimensions are overlooked. We employed a qualitative, constructivist approach drawing on in-depth interviews, observation, and documentation, with findings analyzed through data triangulation. Pierre Bourdieu’s (1977) theory of habitus serves as the main framework for explaining how social dispositions inform cooperative governance. The research was conducted in two pilot villages in Lampung, Rejomulyo and Bumisari. The findings indicate that cooperative success depends heavily on a village’s socio-economic character. In Rejomulyo, where most residents are farmers, cooperatives are most effective when focused on agriculture, whereas in Bumisari, which rests on micro, small, and medium enterprises, services, and trade, cooperatives develop along those lines. Cooperatives concentrate on absorbing local farm produce, selling fertilizer, operating minimarkets, and opening pharmacies, yet remain hesitant to offer savings and loan services. Challenges include limited capital, a small membership base, limited human-resource capacity, restricted access to partnerships, weak coordination with local governments, and competition from loan sharks and middlemen. The community’s collective habitus—marked by patronage, kinship ties, and social hierarchy—shapes cooperative governance. We argue that attending to local habitus is essential to strengthening cooperative institutions more adaptively and sustainably.